The Physical and Psychosocial Risk Factors of WRMSDs AmongNurses in Hospital: A Systematic Review - Wahyu Tri Prayogi; Iwan Muhamad Ramdan; Ida Ayu Indira Dwika Lestari (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Nurses are one of the professions most vulnerable to musculoskeletal pain due to their physically demanding clinical work, which involves prolonged standing, walking, heavy lifting (e.g., carrying patients, medical equipment), and repetitive movements. Objective : The aim of this study was to investigate the prevalence of musculoskeletal disorders at body region on nurses and its associated physical and psychosocial factors in the workplace. Research Methods/ Implementation Methods : This study is a systematic review of the prevalence of WRMSDs and their association with physical and psychosocial factors in nurses. The study was designed using reporting methods based on the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. Results : A review shows that the prevalence of WRMSDs in nurses is very high, ranging from 77%– 97%, with the most frequently affected locations being the lower back, neck, and shoulders. The most frequently reported physical factors are significantly associated with: awkward postures, lifting or moving patients, lack of assistive devices, long work hours and inadequate rest, and understaffing. Psychosocial factors have a significant direct or indirect influence on WRMSDs in many studies: job stress and high psychological demands, lack of social support, work-family conflict, poor leadership, and anxiety or burnout. Conclusion/Lesson Learned : WRMSDs are the most common occupational health problem among nurses. Physical and psychosocial factors contribute significantly, both independently and mutually reinforcing. Effective prevention must include multidimensional interventions, including: Improved work ergonomics (assistive devices, work positions, task rotation), workload management and shift schedules, increased social support and positive leadership, and stress management and psychological well-being programs.